Pseudomonas Species Diversity Along the Danube River Assessed by rpoD Gene Sequence and MALDI-TOF MS Analyses of Cultivated Strains - Mulet, Magdalena; Montaner, María; Román, Daniela; Gomila, Margarita; Kittinger, Clemens; Zarfel, Gernot; Lalucat, Jorge; García-Valdés, Elena (Frontiers in Microbiology, 2020)
A collection of 611 Pseudomonas isolated from 14 sampling sites along the Danube River were identified previously by MALDI-TOF MS with the VITEK MS system and were grouped in 53 clusters by their main protein profiles. The strains were identified in the present study at the phylospecies level by rpoD gene sequencing. Partial sequences of the rpoD gene of 190 isolates representatives of all clusters were analyzed. Strains in the same MALDI-TOF cluster were grouped in the same phylospecies when they shared a minimum 95% similarity in their rpoD sequences. The sequenced strains were assigned to 34 known species (108 strains) and to 32 possible new species (82 strains). The 611 strains were identified at the phylospecies level combining both methods. Most strains were assigned to phylospecies in the Pseudomonas putida phylogenetic group of species. Special attention was given to 14 multidrug resistant strains that could not be assigned to any known Pseudomonas species and were considered environmental reservoir of antibiotic resistance genes. Coverage indices and rarefaction curves demonstrated that at least 50% of the Pseudomonas species in the Danube River able to grow in the isolation conditions have been identified at the species level. Main objectives were the confirmation of the correlation between the protein profile clusters detected by MALDI-TOF MS and the phylogeny of Pseudomonas strains based on the rpoD gene sequence, the assessment of the higher species discriminative power of the rpoD gene sequence, as well as the estimation of the high diversity of Pseudomonas ssp. along the Danube river. This study highlights the Pseudomonas species diversity in freshwater ecosystems and the usefulness of the combination of MALDI-TOF mass spectrometry for the dereplication of large sets of strains and the rpoD gene sequences for rapid and accurate identifications at the species level.